Morphological characterization of Gac Fruit (Momordica cochinchinensis SPRENG) based on qualitative and quantitative traits - Othman, Halimaton Saadiah; Mohd Khairi, Nurin Nazihah (Penerbit Universiti Sultan Zainal Abidin, 2023)
Momordica cochinchinensis is a fruit which originated from South-East Asia and it is a newly introduced crop in Malaysia. It is a superfruit with high nutritional and medicinal properties. However, being an introduced crop, gac fruit is a less-known fruit in Malaysia. A study was conducted in International Islamic University Malaysia (IIUM), Kuantan Pahang involving a total of four gac fruit accessions. The objective of this study was to characterize gac fruit morphology involving qualitative and quantitative morphological traits. Completely randomized design with five replications was used. Based on qualitative traits, variations were observed in parameters such as leaf color, leaf venation, leaf apices, leaf bases, fruit shape and spike density. Generally, the gac fruits were reddish-orange in color, the leaf was dark green on the adaxial part and light green on the abaxial part, and the female and male flower was light yellow and white in color. Analysis of variance revealed significant differences (P<0.05) among accessions in all quantitative traits evaluated. The fruit weight ranged from 193.72 g (Gac Damansara, GD) to 334.70 g (Gac Hulu Langat, GH), fruit length ranged from 9.42 cm (Gac Damansara, GD) to 12.13 cm (Gac Hulu Langat, GH), leaf size ranged from 218.43 cm2 (Gac Damansara, GD) to 337.96 cm2 (GM) and seed weight ranged from 1.43g (Gac Melaka, GM) to 3.94g (Gac Kuantan, GX). Overall, the study revealed significant morphological differences among the accessions evaluated, indicating genotypic diversity that can be incorporated into breeding programs.